Method for synthesizing 4-hydroxycyclopentyl-2-ketene through furfuryl alcohol rearrangement
The synthesis of 4-hydroxycyclopent-2-enone from furfuryl alcohol using solid base catalysts in a stainless steel autoclave addresses yield and cost issues, enabling efficient and cost-effective industrial production.
Patent Information
- Application Number
- CN202411228880.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
AI Technical Summary
The production capacity of 4-hydroxycyclopent-2-enone is limited, and existing methods face challenges such as low yield, high energy consumption, complex catalyst preparation, and high cost, making them unsuitable for practical applications.
A method for synthesizing 4-hydroxycyclopent-2-enone through the rearrangement of furfuryl alcohol using a solid base catalyst, such as ZnO, hydroxyapatite, or XY-type bimetallic hydrotalcite, in a stainless steel autoclave under controlled conditions, achieving a one-step reaction with high yield and mild conditions.
The method achieves a high conversion rate of furfuryl alcohol into 4-hydroxycyclopent-2-enone with excellent selectivity, suitable for industrial production, and reduces energy consumption and catalyst complexity.
Smart Images

Figure BDA0005025497800000021 
Figure BDA0005025497800000022 
Figure BDA0005025497800000091
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing 4-hydroxycyclopent-2-enone by rearrangement of furfuryl alcohol, and belongs to the technical field of chemical preparation. Background Art
[0002] α, β-unsaturated carbonyl compounds are important components of natural products, drug molecules and bulk chemicals, and are also universal synthetic reactants in a variety of organic transformations (such as Michael addition, Diels-Alder and Heck reactions) because these compounds contain active olefins, carbonyl groups and hydroxyl groups in a small cyclopentyl molecule. Among them, 4-hydroxycyclopent-2-enone is a valuable intermediate for the synthesis of natural products and analogs. Therefore, the synthesis of 4-hydroxycyclopent-2-enone is a hot topic in organic chemistry research. Unfortunately, the production capacity of 4-hydroxycyclopent-2-enone is very limited and far from meeting the application needs in various fields. Therefore, it is of great significance to find a green and renewable synthetic process route for the production of 4-hydroxycyclopent-2-enone using bulk chemicals as raw materials.
[0003] With the increasing consumption of non-renewable fossil resources and the demand for green chemistry, biomass resources have been widely studied. In recent years, there have been increasing efforts to establish new technologies for converting biomass into fuels or basic chemicals, which can be further used in the production of fine chemicals, materials or pharmaceuticals. Considering the non-renewability of petroleum resources, it is of great significance to develop new technologies for the synthesis of renewable 4-hydroxycyclopent-2-enone from biomass. Furfuryl alcohol is an important biomass platform compound, which has been industrially produced using the hemicellulose fraction of agricultural waste and forest waste as raw materials. Furfuryl alcohol can be converted into 4-hydroxycyclopent-2-enone. Many schemes have been developed for this conversion. For example, Hronec's research group reported that furfuryl alcohol can be converted into 4-hydroxycyclopent-2-enone (HCP) under the catalysis of hydrogen protons formed by water self-dissociation at high temperature (180-200°C) (Journal of Industrial and Engineering Chemistry, 2014, 20 (2): 650-655.) Unfortunately, the yield of HCP is very low (i.e., about 50%). Zhang's team used catalysts such as liquid alkali or calcium oxide to reduce the concentration of hydrogen protons generated by in situ water at 240°C (Green Chemistry, 2016, 18 (12): 3607-3613). Although the conversion of furfuryl alcohol was reduced, the selectivity of HCP was improved, and the yield of HCP was about 80%. However, the reaction temperature (240°C) and energy consumption in this work were high, and the furfuryl alcohol concentration in the reaction was low (10wt.%), which is not conducive to production in practical applications. Zou's team synthesized a pure solid Lewis acid catalyst, and carried out the furfuryl alcohol rearrangement reaction at 150°C in a water / n-hexane biphasic solvent system (Green Chemistry, 2020, 22(8): 2549-2557), with a yield of HCP of about 88%. However, in this work, the concentration of furfuryl alcohol in the system was also very low (about 5wt.%), and there were disadvantages such as complex catalyst preparation process, expensive catalyst materials, and high cost. Because, in this reaction process, some polymers are easily produced. As the concentration of furfuryl alcohol in the system gradually increases, this phenomenon becomes more serious, resulting in a gradual decrease in the yield of the target product - 4-hydroxycyclopent-2-enone. Therefore, the present invention has a reaction temperature of 200°C, and the concentration of furfuryl alcohol in the system (20wt.%) and the yield (91%) are higher than those previously reported. At the same time, it has the additional advantages of simple catalyst preparation method, low cost, mild reaction conditions, and good stability. This makes the application conducive to industrial production and practical. Summary of the invention
[0004] In view of the above technical problems, the present invention provides a method for synthesizing 4-hydroxycyclopent-2-enone by rearrangement of furfuryl alcohol. Under the action of a solid base catalyst, furfuryl alcohol is converted into the target product 4-hydroxycyclopent-2-enone in one step in a stainless steel autoclave, thereby providing a novel, simple and efficient synthesis method for preparing 4-hydroxycyclopent-2-enone from furfuryl alcohol in one step.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for synthesizing 4-hydroxycyclopent-2-enone, which is as follows:
[0007] Furfuryl alcohol is used as a raw material, and an aqueous phase rearrangement reaction occurs under the action of a solid base catalyst, so that the 4-hydroxycyclopent-2-enone is obtained by a one-step reaction; wherein the solid base catalyst comprises ZnO, hydroxyapatite, XY-type bimetallic hydrotalcite and supported zinc oxide.
[0008] The chemical structural formulas of the above-mentioned raw material furfuryl alcohol and the target product 4-hydroxycyclopent-2-enone are shown in Table 1
[0009]
[0010] The reaction pathway of the present invention is shown in the figure.
[0011]
[0012] Furthermore, in the above technical scheme, the reaction is carried out in a batch reactor, water and a solid base catalyst are placed in a stainless steel autoclave; the amount ratio of water to solid base catalyst is 40g: 2mg-14mg; (preferably 2mg-11mg, more preferably 5mg-8mg), the air in the reactor is excluded (the reactor is purged with nitrogen 6 times), the reaction temperature is 180-240°C (preferably 190-235°C, more preferably 200-220°C), the concentration of furfuryl alcohol aqueous solution is 10wt.%-50wt.% (preferably 10wt.%-40wt.%, more preferably 10wt.%-30wt.%), and the reaction time is 4 to 5min.
[0013] Furthermore, in the above technical scheme, the XY type bimetallic hydrotalcite includes ZnAl-HT, ZnNi-HT, ZnCo-HT, NiAl-HT, CoAl-HT, NiFe-HT, and the theoretical atomic ratio of X / Y is 1-5:1 (preferably 1-4:1; more preferably 1-3:1); the supported zinc oxide is ZnO / ZrO2, and the supporting amount is 5wt%-13wt%.
[0014] Furthermore, in the above technical solution, the XY type hydrotalcite-like catalyst uses Zn(NO3)2·6H2O, Ni(NO3)2·6H2O, Al(NO3)3·9H2O, Co(NO3)2·6H2O and Fe(NO3)3·9H2O as precursors, and synthesizes hydrotalcite-like compounds by coprecipitation under low supersaturation conditions, and their X / Y theoretical atomic ratio is 1-5:1 (preferably 1-4:1; more preferably 1-3:1). X nitrate is selected from Zn(NO3)2·6H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O; Y nitrate solution is selected from Al(NO3)3·9H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O, Fe(NO3)3·9H2O; X and Y are different.
[0015] Furthermore, in the above technical solution, the XY-type bimetallic hydrotalcite is prepared by a sedimentation precipitation method.
[0016] The specific process is as follows: according to the range of theoretical atomic number ratio of X / Y, X nitrate solution and Y nitrate solution are mixed; the concentration of X nitrate in the mixed solution is 1-4M, and the concentration of Y nitrate solution is 1M; then the mixed solution is slowly dripped into 2M sodium carbonate or sodium carbonate and sodium hydroxide aqueous solution at 30-110° C. (preferably 40-100° C., more preferably 50-90° C.) (the volume ratio of the mixed solution to sodium carbonate or the mixed aqueous solution of sodium carbonate and sodium hydroxide is 1:1), and the solution is rapidly stirred under the condition of controlling the pH value to 9-12, and the pH is adjusted by continuously adding 1M precipitant Na2CO3 or NaOH solution. Aging at 70-90°C for 18h-24h, drying in an oven at 80-200°C for 4-48h, and then calcining at 300-800°C (preferably 350-750°C, more preferably 400-700°C) for 0.5-10h (preferably 1-8h, more preferably 1-6h), wherein the precipitant is Na2CO3 or NaOH, to obtain an XY-type bimetallic hydrotalcite catalyst;
[0017] Furthermore, in the above technical solution, the supported zinc oxide catalyst is prepared by an impregnation method, and the specific process is as follows: the carrier component ZrO2 is synthesized by a coprecipitation method before impregnation, and is heated at 100-700°C (preferably 200-
[0018] 650℃, more preferably 250-600℃) pretreatment for 1-24h (preferably 1.5-20h, more preferably 2-15h), the impregnation liquid is an aqueous solution of a soluble zinc salt, the pretreated carrier component ZrO2 is impregnated with the impregnation liquid once or multiple times, after impregnation for 1-36h (preferably 2-30h, more preferably 3-24h), it is dried at 50-150℃ for 4-48h, and then calcined at 200-800℃ (preferably 300-750℃, more preferably 350-700℃) for 0.1-10h (preferably 0.5-8h, more preferably 1-6h), and the mass percentage of zinc oxide is controlled within the range of 1-85% (preferably 2-75%, more preferably 3-65%). The supported zinc oxide catalyst is obtained.
[0019] The beneficial effects of this application include:
[0020] 1. The method of the present invention has few operating steps and can directly obtain 4-hydroxycyclopent-2-enone from furfuryl alcohol through an aqueous phase reaction in one step. It is a green and simple synthetic route. At the same time, the preparation method of the catalyst is simple, the reaction conditions are mild, and the stability is good. The conversion rate of furfuryl alcohol is generally high, and the selectivity of 4-hydroxycyclopent-2-enone is excellent, and it can be used for actual industrial production.
[0021] 2. The present invention adopts a stainless steel intermittent reactor, which can convert furfuryl alcohol into 4-hydroxycyclopent-2-enone under the action of a catalyst, and has the advantages of simple process route, high operability, low energy consumption, simple catalyst preparation and low environmental pollution.
[0022] 3. The present invention prepares and uses a series of XY-type bimetallic hydrotalcite catalysts to convert furfuryl alcohol into
[0023] 4-Hydroxycyclopent-2-enone can be directly synthesized into high value-added 4-hydroxycyclopent-2-enone in one step through an aqueous phase rearrangement reaction in a stainless steel batch reactor at a constant temperature, and the concentration and yield of furfuryl alcohol in the system are higher than those previously reported. At the same time, the furfuryl alcohol conversion rate can reach more than 95%, which can be used for actual industrial production and has good catalytic performance.
[0024] 4. This study transforms furfuryl alcohol into 4-hydroxycyclopent-2-enone through aqueous rearrangement.
[0025] Enone is a valuable intermediate for synthesizing natural products and analogs. The present invention is further improved and innovated compared with the previous ones. The reaction is carried out at a lower temperature (200°C) and the concentration of furfuryl alcohol in the system is increased (20wt.%), and the yield (91%) is higher than the previous reports. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1It is the liquid chromatogram of the product of synthesizing 4-hydroxycyclopent-2-enone from furfuryl alcohol in Example 4 and Example 8.
[0027] Figure 2 The liquid chromatogram of the product of synthesizing 4-hydroxycyclopent-2-enone from furfuryl alcohol in Comparative Example 2 and Example 3 Figure 3 This is a mass spectrum comparison chart of the target product 4-hydroxycyclopent-2-enone obtained in Example 4. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0029] Example 1
[0030] (1) Commercial amphoteric metal oxide ZnO (purchased from Tianjin Guangfu Technology Development Co., Ltd.) was used as a catalyst.
[0031] (2) 5 mg of the above ZnO catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times and the reaction temperature was 200°C. A high pressure liquid chromatography pump (feed time 1 min, feed rate 20 mL min) was used. -1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50°C. The conversion rate of furfuryl alcohol was 100%, and the yield of 4-hydroxycyclopent-2-enone was 80%.
[0032] Comparative Example 2
[0033] (1) Commercial K3PO4 (purchased from Aladdin Chemical Reagent Co., Ltd.) was used as a catalyst.
[0034] (2) 5 mg of the above K3PO4 catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times and the reaction temperature was 200°C. A high pressure liquid chromatography pump (feed time 1 min, feed rate 20 mL min) was used. -1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50°C. The conversion rate of furfuryl alcohol was 80%, and the yield of 4-hydroxycyclopent-2-enone was 55%.
[0035] Example 3
[0036] (1) Commercial solid base hydroxyapatite (HAP) (purchased from Aladdin Chemical Reagent Co., Ltd.) was used.
[0037] (2) 5 mg of the above HAP catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times and the reaction temperature was 200°C. A high pressure liquid chromatography pump (feed time 1 min, feed rate 20 mL min) was used. -1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50°C. The conversion rate of furfuryl alcohol was 100%, and the yield of 4-hydroxycyclopent-2-enone was 85%.
[0038] Example 4
[0039] (1) Preparation of solid base ZnAl-HT catalyst: 20 mL of Zn(NO3)2·6H2O (11.8526 g) and Al(NO3)3·9H2O (7.4911 g) nitrate solutions (2 M and 1 M, respectively) were dropped into 20 mL of distilled water containing 2 M Na2CO3 (4.2384 g). The mixture was stirred rapidly at a constant pH of 10 and the pH was adjusted by continuously adding 1 M NaOH solution. Once the gel was obtained, it was aged at 80°C for 24 h and then centrifuged. The solid was washed with distilled water until the pH was neutral. The hydrotalcite-like material was dried in an oven for 24 h (70°C) and then air calcined (air flow rate: 100 mL·min --1 ), the heating rate is 5℃·min -1 , the calcination temperature can reach up to 500℃.
[0040] (2) 5 mg of the above ZnAl-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times, and the reaction temperature was 200°C. A high pressure liquid chromatography pump (feed time 1 min, feed rate 20 mL min) was used. -1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50° C. The conversion rate of furfuryl alcohol was 100%, and the yield of 4-hydroxycyclopent-2-enone was 91%.
[0041] Example 5
[0042] (1) Preparation of solid base ZnNi-HT catalyst: 20 mL of Zn(NO3)2·6H2O (11.8526 g) and Ni(NO3)2·6H2O, (5.8162 g) nitrate solutions (2 M and 1 M, respectively) were dropped into 20 mL of distilled water containing 2 M Na2CO3 (4.2384 g). The mixture was stirred rapidly at a constant pH of 10 and the pH was adjusted by continuously adding 1 M NaOH solution. Once the gel was obtained, it was aged at 80°C for 24 h and then centrifuged. The solid was washed with distilled water until the pH was neutral. The hydrotalcite-like material was dried in an oven for 24 h (70°C) and then air-roasted for pretreatment (100 mL·min -1 ), the heating rate is 5℃·min -1 , up to 500℃.
[0043] (2) 5 mg of the above ZnNi-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times, and the reaction temperature was 200°C. A HPLC pump (Elite P270, HPLC) was used, with a feed time of 1 min and a feed rate of 20 mL min -1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50° C. The conversion rate of furfuryl alcohol was 100%, and the yield of 4-hydroxycyclopent-2-enone was 88%.
[0044] Example 6
[0045] (1) Preparation of solid base ZnCo-HT catalyst: 20 mL of Zn(NO3)2·6H2O (11.8526 g) and Co(NO3)2·6H2O, (5.8207 g) nitrate solutions (2 M and 1 M, respectively) were dropped into 20 mL of distilled water containing 2 M Na2CO3 (4.2384 g). The mixture was stirred rapidly at a constant pH of 10 and the pH was adjusted by continuously adding 1 M NaOH solution. Once the gel was obtained, it was aged at 80°C for 24 h and then centrifuged. The solid was washed with distilled water until the pH was neutral. The hydrotalcite-like material was dried in an oven for 24 h (70°C) and then air-treated (100 mL·min -1 ), the heating rate is 5℃·min -1 , up to 500℃.
[0046] (2) 5 mg of the above ZnCo-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times, and the reaction temperature was 200°C. A HPLC pump (Elite P270, feed time 1 min, feed rate 20 mL min) was used.-1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50° C. The conversion rate of furfuryl alcohol was 100%, and the yield of 4-hydroxycyclopent-2-enone was 84%.
[0047] Example 7
[0048] (1) Preparation of solid base NiAl-HT catalyst: 20 mL of Ni(NO3)2·6H2O (11.6342 g) and Al(NO3)3·9H2O (7.4911 g) nitrate solutions (2 M and 1 M, respectively) were dropped into 20 mL of distilled water containing 2 M Na2CO3 (4.2384 g). The mixture was stirred rapidly at a constant pH of 10 and the pH was adjusted by continuously adding 1 M NaOH solution. Once the gel was obtained, it was aged at 80°C for 24 h and then centrifuged. The solid was washed with distilled water until the pH was neutral. The hydrotalcite-like material was dried in an oven for 24 h (70°C) and then air-treated (100 mL·min -1 ), the heating rate is 5℃·min -1 , up to 500℃.
[0049] (2) 5 mg of the above NiAl-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times, and the reaction temperature was 200°C. A HPLC pump (Elite P270, HPLC) was used, with a feed time of 1 min and a feed rate of 20 mL min -1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50°C. The conversion rate of furfuryl alcohol was 97%, and the yield of 4-hydroxycyclopent-2-enone was 70%.
[0050] Example 8
[0051] (1) Preparation of solid base CoAl-HT catalyst: 20 mL of Co(NO3)2·6H2O (11.6414 g) and Al(NO3)3·9H2O (7.4911 g) nitrate solutions (2 M and 1 M, respectively) were dropped into 20 mL of distilled water containing 2 M Na2CO3 (4.2384 g). The mixture was stirred rapidly at a constant pH of 10 and the pH was adjusted by continuously adding 1 M NaOH solution. Once the gel was obtained, it was aged at 80°C for 24 h and then centrifuged. The solid was washed with distilled water until the pH was neutral. The hydrotalcite-like material was dried in an oven for 24 h (70°C) and then air-treated (100 mL·min -1 ), the heating rate is 5℃·min -1 , up to 500℃.
[0052] (2) 5 mg of the above CoAl-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times, and the reaction temperature was 200°C. A HPLC pump (Elite P270, 1 min feeding time, 20 mL min feeding rate) was used. -1 ), 20mL of 20wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4-5min. After the reaction, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50°C. The conversion rate of furfuryl alcohol was 94%, and the yield of 4-hydroxycyclopent-2-enone was 69%.
[0053] Example 9
[0054] (1) Preparation of solid base XY type catalyst NiFe-HT catalyst: 20 mL of Ni(NO3)2·6H2O (11.6342 g) and Fe(NO3)3·9H2O (8.0799 g) nitrate solutions (2 M and 1 M, respectively) were dropped into 20 mL of distilled water containing 2 M Na2CO3 (4.2384 g). The mixture was stirred rapidly at a constant pH of 10 and the pH was adjusted by continuously adding 1 M NaOH solution. Once the gel was obtained, it was aged at 80°C for 24 h and then centrifuged. The solid was washed with distilled water until the pH was neutral. The hydrotalcite-like material was dried in an oven for 24 h (70°C) and then air-treated (100 mL·min -1 ), the temperature slope is 5℃·min -1 , up to 500℃.
[0055] (2) 5 mg of the above NiFe-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times, and the reaction temperature was 200°C. A HPLC pump (Elite P270, HPLC) was used, with a feed time of 1 min and a feed rate of 20 mL min. -1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the temperature of the reactor was rapidly cooled with cold water to about 50° C. The conversion rate of furfuryl alcohol was 97%, and the yield of 4-hydroxycyclopent-2-enone was 71%.
[0056] Example 10
[0057] (1) Preparation of supported metal oxide catalytic ZnO / ZrO2: In a typical synthesis of ZrO2 nanoparticles, 5.8 g ZrOCl2.8H2O was first dissolved in 100 mL of double distilled water, and then 1 M NaOH solution was gradually added to keep the pH at 10.5. The solution was then stirred on a stirrer for 24 h, and the resulting white precipitate was centrifuged 4-5 times to remove the water-soluble NaCl in the solution. The resulting product was then placed in a stainless steel autoclave and freeze-dried at 200 °C for 6 h. The resulting product was calcined at 350 °C for 5 h and ground into zirconium oxide nanoparticles with a mortar and pestle. Supported ZnO / ZrO2 catalysts were prepared by wet impregnation. ZrO2 carriers were synthesized according to the above coprecipitation method. ZrO2 (1 g) was stoichiometrically immersed in 25 mL of Zn(NO3)2 aqueous solution for 6 h, dried at 110 °C for 24 h, and then calcined in air at 500 °C for 3 h.
[0058] (2) 5 mg of the above ZnO / ZrO2 catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times, and the reaction temperature was 200°C. A HPLC pump (Elite P270, HPLC) was used, with a feed time of 1 min and a feed rate of 20 mL min -1 ), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5 min. After the reaction was completed, the heating was turned off and the reaction was immediately quenched, and cold water was passed twice to reduce the temperature to about 50°C. The conversion rate of furfuryl alcohol was 98%, and the yield of 4-hydroxycyclopent-2-enone was 78%.
[0059] The experimental results of the above-mentioned embodiments 1-10 are shown in Table 2.
[0060] Table 2 Synthesis of 4-hydroxycyclopent-2-enone from furfuryl alcohol
[0061]
[0062] Examples 11-19
[0063] Using the ZnAl-HT in Example 4 as the catalyst, 5 mg of ZnAl-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times and the reaction mixture was stirred using an HPLC pump (Elite P270, feed time 1 min, feed rate 20 mL min -1 ), 20mL of 10 / 20wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction time was 4 to 5min. The results of the test at different reaction temperatures and the reaction results are shown in Tables 3 and 4.
[0064] Table 3 In a 10 wt.% furfuryl alcohol aqueous solution at different reaction temperatures, ZnAl-HT catalyzes the rearrangement of furfuryl alcohol to produce 4-hydroxycyclopent-2-enone.
[0065]
[0066] Table 4 In a 20 wt.% furfuryl alcohol aqueous solution at different reaction temperatures, ZnAl-HT catalyzes the rearrangement of furfuryl alcohol to produce 4-hydroxycyclopent-2-enone.
[0067]
[0068] Examples 20-23
[0069] Using the ZnAl-HT in Example 4 as the catalyst, 5 mg of ZnAl-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times and the reaction mixture was stirred using an HPLC pump (Elite P270, feed time 1 min, feed rate 20 mL min -1 ), the reaction temperature is 200°C, and the reaction time is 4 to 5 minutes. The results of the test under different concentrations of furfuryl alcohol aqueous solution and the reaction results are shown in Table 5
[0070] Table 5 Rearrangement of furfuryl alcohol to 4-hydroxycyclopent-2-enone catalyzed by ZnAl-HT in the presence of different concentrations of furfuryl alcohol aqueous solution
[0071]
[0072] Examples 24-28
[0073] Using the ZnAl-HT in Example 4 as the catalyst, 5 mg of ZnAl-HT catalyst and 40 g of water were placed in a stainless steel autoclave. The reactor was purged with nitrogen for 6 times and the reaction mixture was stirred using an HPLC pump (Elite P270, feed time 1 min, feed rate 20 mL min -1), 20 mL of 20 wt.% furfuryl alcohol aqueous solution (Sinopharm Chemical Reagent Co., Ltd.) was injected into the reactor. The reaction temperature was 200°C and the reaction time was 4 to 5 min. The results of the test under different catalyst dosages and the reaction results are shown in Table 6.
[0074] Table 6 Rearrangement of furfuryl alcohol to 4-hydroxycyclopent-2-enone catalyzed by ZnAl-HT at different catalyst dosages
[0075]
[0076] It can be seen from the above examples that 4-hydroxycyclopent-2-enone with high added value can be directly synthesized in one step by using furfuryl alcohol as a raw material through an aqueous phase rearrangement reaction, and the concentration (20wt.%) and yield (91%) of furfuryl alcohol in the system are higher than those previously reported. At the same time, the furfuryl alcohol conversion rate can reach more than 95%, and the catalyst has the additional advantages of simple preparation method, low cost, mild reaction conditions, and good stability. This application is conducive to industrial production and has practicality.
Claims
1. A method for synthesizing 4-hydroxycyclopent-2-enone, characterized in that: The method is as follows: Using furfuryl alcohol as a raw material, an aqueous phase rearrangement reaction occurs under the action of a solid base catalyst, and the 4-hydroxycyclopent-2-enone is obtained by a one-step reaction; The solid base catalysts include ZnO, hydroxyapatite, XY-type bimetallic hydrotalcite and supported zinc oxide.
2. The method according to claim 1, characterized in that: The reaction is carried out in a batch reactor, water and a solid base catalyst are placed in a stainless steel autoclave; The ratio of water to solid base catalyst is 40g:2mg-14mg; the air in the reactor is excluded, the reaction temperature is 180-240°C, the concentration of furfuryl alcohol aqueous solution is 10wt.%-50wt.%, and the reaction time is 4-5min.
3. The method according to claim 1 or 2, characterized in that: XY-type bimetallic hydrotalcites include ZnAl-HT, ZnNi-HT, ZnCo-HT, NiAl-HT, CoAl-HT, and NiFe-HT, with a theoretical atomic ratio of X / Y of 1-5:1; supported zinc oxide is ZnO / ZrO 2, The loading amount is 5wt.%-13wt.%.
4. The method according to claim 3, characterized in that: The XY type hydrotalcite-like catalyst uses Zn(NO3)2·6H2O, Ni(NO3)2··6H2O, Al(NO3)3·9H2O, Co(NO3)2·6H2O and Fe(NO3)3·9H2O as precursors, and synthesizes hydrotalcite-like compounds by co-precipitation method under low supersaturation conditions, and their X / Y theoretical atomic ratio is 1-5:
1.
5. The method according to claim 4, characterized in that: XY bimetallic hydrotalcite was prepared by sedimentation precipitation method. The specific process is as follows: according to the X / Y theoretical atomic ratio range, X nitrate and Y nitrate solutions are mixed; The molar ratio of X nitrate to Y nitrate in the mixed solution is 1-4:1, and then the mixed solution is slowly dripped into sodium carbonate or sodium carbonate and sodium hydroxide aqueous solution at 30-110°C, and rapidly stirred under the condition of controlling the pH value to be 9-12, and the pH is adjusted by continuously adding 1M precipitant Na2CO3 or NaOH solution; aging at 70-90°C for 18h-24h, drying in an oven at 80-200°C for 4-48h, and then calcining at 300-800°C for 0.5-10h to obtain an XY type bimetallic hydrotalcite catalyst.
6. The method according to claim 3, characterized in that: The supported zinc oxide catalyst is prepared by an impregnation method, and the specific process is: the support component ZrO2 is synthesized by a coprecipitation method before impregnation, and is pretreated at 100-700°C for 1-24 hours. The impregnation liquid is an aqueous solution of a soluble zinc salt. The pretreated support component ZrO2 is impregnated with the impregnation liquid once or multiple times. After impregnation for 1-36 hours, it is dried at 50-150°C for 4-48 hours, and then calcined at 200-800°C for 0.1-10 hours. The mass percentage of zinc oxide is controlled within the range of 1-85%, and the supported zinc oxide catalyst is obtained.
